PENGARUH PERUBAHAN TUTUPAN LAHAN TERHADAP KETERSEDIAAN AIR DI DAS JLANTAH HULU KABUPATEN KARANGANYAR TAHUN 2009-2013 (IMPLEMENTASI SEBAGAI SUPLEMEN PEMBELAJARAN GEOGRAFI KELAS X PADA MATERI POKOK HUBUNGAN MANUSIA DAN LINGKUNGAN AKIBAT DINAMIKA HIDROSFER) - Erlangga, Gigih (Pendidikan Geografi, 2015)
This study is aimed to know(1) land cover changes in Jlantah Upperland Watershed, (2) condition of water supplies in Jlantah Upperland Watershed Karanganyar Regency 2009-2013, (3) the effect of land cover changes for water supplies in Jlantah Upperland Watershed, (4) give a sign and recommendation for land cover based on each part of Jlantah Upperland Watershed 2009-2013, (5) make an Implementation For Geographical Suplement Educate On A Base Competencies Of Relationship Between Human And Environment As A Result of Hydrosfer Dynamics : For Senior High School Grade X.This research was a descriptive study used spatial approach with part of Jlantah Upperland Watershed as a unit analysis and organized with survey on a fields. All of part of Jlantah Upperland Watershed as a study to know the condition of water supplies explained by each part of watershed such as its upperland, middleland and lownland to get the spreads of one variability on this study, water supplies. Sampling techniques with purposive sampling. Data collecting with survey on a fileds, interviews, laboratory test and documentation analysis. Data analysis techniques with descriptive include spatial relationship between condition of land cover changes in Jlantah Upperland Watershed with water supplies of Jlantah Upperland Watershed 2009-2013.Based on data analysis, the result of this research are : (1) Landcover changes happened in Jlantah Upperland Watershed with the biggest changing was grassland (-119,98 Ha) and unbuild land (+115,90 Ha) in a periode of 2009-2013, (2) Water supplies changes happened in Jlantah Upperland Watershed happened on 2010 with 63.548.975 m3/yr, supported by 53.172.414 m3/yr from the upperland, (3)Percentages Landcover changes in Jlantah Upperland was -1,73% caused decreasing of water supplies for 27%, (4) Signed and reccomendation gave by each part of Jlantah Upperland Watershed, the upperland with 100% yearly vegetation, the middleland with 25% maximum of seasonal vegetation and 75% yearly vegetation,the downland with 50% of each types include of seasonal vegetation and yearly vegetation, (5) Final results of this research could use for Implementation For Geographical Suplement Educate On A Base Competencies Of Relationship Between Human And Environment As A Result of Hydrosfer Dynamics : For Senior High School Grade X.Keywords : Spatial correlation, land cover changes, water supplies, sign and recommendation